Dynamic Response Analysis of Lateral Impact Force of Frame Wharf with Rock-Socketed Piles in Inland River Steel Sheath. (6th December 2019) - Zhang, Xiaolong; Duan, Bingchuan; Wang, Chengzhi; Wang, Duoyin
Abstract : In this study, a three-dimensional finite element model was established to simulate the dynamic response of a large-scale steel-reinforced concrete composite high-pile wharf with a rock-socketed steel sheath. The model is based on the second phase of the Chongqing Orchard Harbor structure project in conjunction with the project "Research on the mechanism of interface damage and energy dissipation of the structure of the large-scale steel-reinforced concrete composite high-pile wharf in inland waters." The stiffness of frame wharf is studied from the perspective of modal and transient dynamic analysis of structural dynamics. The distribution of the low-order modal frequency is more uniform. With the increase of the order, the modal frequency of the structure shows a periodical jump. The overall stiffness of the frame structure is larger with the steel sheath, and the longitudinal stiffness is less than the transverse stiffness. Under the action of transverse impact load, the members and joints of the steel-concrete structure exhibit synchronous mechanical response characteristics in the time domain. The peak values of displacement and stress of the structural joints occur 0.05 s after the peak value of the load-time history, and the peak value of reverse response of force occurs at 2.3 s, which is markedly smaller than the peak value of the response of load direction. Reducing the local positional stiffness of the load point is beneficial to improve the stress of the entire structure. The weak links of the frame structure appear at the joints of the members. Because of the hoop action of the steel sheath, the stress of the reinforced concrete pile core is more uniform. The peak value of the equivalent stress of the steel sheath member is generally larger than that of the reinforced concrete pile core, and the stress is highly concentrated at the joints of the steel tube longitudinal and transverse braces.